Republicanism and Anticlerical Nationalism in Spain - Sanabria, E. author. aut Link
XIII, 258 p.
Keywords: This book analyzes attempts by radical Spanish republicans to construct an anticlerical-nationalist vision of Spain, focusing in particular on the the mass production by the 'anticlertical industry' of newspapers, novels, poems, cartoons, posters, postcards and plays put out by republican muckrakers, journalists, and politicians.